Antimicrobial Effect of Lactobacillus reuteri on Cariogenic Bacteria Streptococcus gordonii, Streptococcus mutans,and Periodontal Diseases Actinomyces naeslundii and Tannerella forsythia - Baca Castañon, Magda Lorena; De la Garza Ramos, Myriam Angélica; Alcázar Pizaña, Andrea Guadalupe; Grondin, Yohann; Coronado Mendoza, Anahí; Sánchez Nájera, Rosa Isela; Cárdenas Estrada, Eloy; Medina de la Garza, Carlos Eduardo; Escamilla García, Erandi (Springer Science+Business Media, 2014)
Lactic acid bacteria (LAB) are well known for their beneficial effects on human health in the intestine and immune system; however, there are few studies on the impact they can generate in oral health. The aim of this study was to test and compare in vitro antimicrobial activity of L. reuteri on pathogenic bacteria involved in the formation of dental caries: S. mutans, S. gordonii, and periodontal disease: A. naeslundii and T. forsythia. Also, we determined the growth kinetics of each bacterium involved in this study. Before determining the antimicrobial action of L. reuteri on cariogenic bacteria and periodontal disease, the behavior and cell development time of each pathogenic bacterium were studied. Once the conditions for good cell growth of each of selected pathogens were established according to their metabolic requirements, maximum exponential growth was determined, this being the reference point for analyzing the development or inhibition by LAB using the Kirby Bauer method. Chlorhexidine 0.12 % was positive control. L. reuteri was shown to have an inhibitory effect against S. mutans, followed by T. forsythia and S. gordonii, and a less significant effect against A. naeslundii. Regarding the effect shown by L. reuteri on the two major pathogens, we consider its potential use as a possible functional food in the prevention or treatment of oral diseases.